2018
DOI: 10.12659/msm.909153
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Polysaccharide Inhibits Ionizing Radiation-Induced Bystander Effects by Regulating MAPK/NF-kB Signaling Pathway in Bone Mesenchymal Stem Cells (BMSCs)

Abstract: BackgroundThis study investigated the effect of Astragalus polysaccharides (APS) on radiation-induced bystander effects (RIBE) in human bone mesenchymal stem cells (BMSCs) induced by irradiated A549 cells.Material/MethodsA549 cells were irradiated with 2 Gy X-rays to obtain conditioned medium. BMSCs were incubated with the conditioned medium or APS. The levels of reactive oxygen species (ROS) and TGF-β were detected by ELISA. Cell survival, genomic instability, and DNA damages were detected by CCK-8 assay, col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…This indicates that APS may protect against genotoxicity in BMSCs exposed to FA. This is consistent with study showing that APS can maintain genomic stability and reduces DNA damage in BMSCs incubated with the irradiated A549 [22,29]. When external factors induce DNA damage, the cells can mobilize corresponding repair mechanisms to reverse these damages in order to maintain genetic stability.…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that APS may protect against genotoxicity in BMSCs exposed to FA. This is consistent with study showing that APS can maintain genomic stability and reduces DNA damage in BMSCs incubated with the irradiated A549 [22,29]. When external factors induce DNA damage, the cells can mobilize corresponding repair mechanisms to reverse these damages in order to maintain genetic stability.…”
Section: Discussionsupporting
confidence: 91%
“…APS has been shown to inhibit cell apoptosis, and reduce the proliferation and differentiation of bone marrow-derived MSCs following ferric ammonium citrate-induced iron overload [21]. Zhang et al reported that APS had protective effects on cell survival level of bystander cells cultured in conditioned medium and maintained the stability of the genome by reducing the number of 53BP1 foci and micronuclei [22]. Current understanding of the effects of APS on bone marrow-derived MSCs in the lung cancer microenvironment remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that APS can reduce the proliferation of bone marrow-derived MSCs caused by ferric ammonium citrate-induced iron overload [21]. Treatment with APS also inhibits ionizing radiation-induced bystander effects in bone marrow-derived MSCs [22], has significant antitumor activity in human lung cancer cells [23], and exerts a protective effect on injury due to inflammation [24]. However, the role of APS in bone marrow-derived MSCs induced by lung cancer cells remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zhang et al used conditioned medium obtained after radiation to culture bone marrow-derived mesenchymal stem cells and observed the effect of RIBEs. They found that the RIBEs in these cells were mediated by ROS, which may be related to the MAPK/NF-κB signaling pathway [113].…”
Section: Double-edged Sword Of the Ros Generation Strategy In Rtmentioning
confidence: 99%